Prometna potražnja i robni tokovi u funkciji integralnog transporta - Ivaković, Čedomir (Promet - Traffic&Transportation)
As a result of an extensive research, different models of review and follow-up/monitoring of transport demand and freight flows have been obtained. Transport demand is either related either to the origin or destination while freight flows may be incoming and outgoing (inward and outward-bound) in (to) a given location or facility, as for instance a container terminal. Furthermore, simulation and mathematical models of monitoring and review of distribution channels and transport flows optimization have been dealt with in this paper.